User Training in University Libraries (Journal of human and social sciences, 2023)
The study dealt with the concept of university libraries, the beneficiary, the training of beneficiaries to access information sources within the library, the objectives of the beneficiaries of training, and the most important justifications that called for providing a training service to the beneficiaries in the university libraries. And the extent of the impact of modern technical developments on the services provided in the university libraries. It also touched on knowing the most important methods used to train beneficiaries of the different types of library services, as well as identifying the most important basic skills that beneficiaries take through training to deal with the contents of the library, and knowing the most important steps necessary to prepare an integrated program for training beneficiaries within libraries, by answering questions related to Readers, library and staff, in addition to identifying the most important obstacles and difficulties facing the service of training beneficiaries, and the study also dealt with experiences about the service of training beneficiaries in some university libraries in a number of Arabic and international countries.
Keywords: User Training; University Libraries; Patron; Information Sources; Technological Developments